2015
DOI: 10.3390/toxics3020224
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic Effects of Platinum Compounds: Studies in vivo on Intracellular Calcium Homeostasis in the Immature Central Nervous System

Abstract: Platinum compounds cause significant clinical neurotoxicity. Several studies highlight neurological complications especially in paediatric oncology patients with Central Nervous System (CNS) and non-CNS malignancies. To understand the toxicity mechanisms of platinum drugs at cellular and molecular levels in the immature brain, which appears more vulnerable to injury than in the adult one, we compared the effects in vivo of the most used platinum compounds, i.e., cisdichlorodiammineplatinum (cisplatin, cisPt), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 122 publications
0
5
0
Order By: Relevance
“…Here, we focus briefly on experimental works carried out by our research group at the Department of Biology and Biotechnology (formerly Animal Biology) of the University of Pavia from 1986 to the present, which have revealed alterations in the immunopositivity for CBPs in developing and adult rats exposed to two platinum compounds, cisplatin (CisPt) and [Pt( O,O′ -acac)(γ-acac)(DMS)] (PtAcacDMS) (Table 2). These studies have highlighted a dynamic decrease in two buffer CBPs, CB and PV, following treatment with both compounds in the hippocampus and cerebellum, and also detected a less severe damage by PtAcacDMS compared to CisPt, demonstrating that CBPs can help discriminate between compounds by providing a reliable estimation of neuronal damage [19,39,186,187,188]. Interestingly, contrary to what was observed in hibernating animals, there is no correlation between changes in CBPs and cytoskeletal detection, as CB immunolabelling decreases while NF-H phosphorylation increases following CisPt treatment [18,188], and is likely responsible for the marked morphological signs of degeneration observed in Purkinje cells of the developing rat cerebellum [189].…”
Section: Hibernation and Translational Medicine: The Case Of Neuromentioning
confidence: 99%
“…Here, we focus briefly on experimental works carried out by our research group at the Department of Biology and Biotechnology (formerly Animal Biology) of the University of Pavia from 1986 to the present, which have revealed alterations in the immunopositivity for CBPs in developing and adult rats exposed to two platinum compounds, cisplatin (CisPt) and [Pt( O,O′ -acac)(γ-acac)(DMS)] (PtAcacDMS) (Table 2). These studies have highlighted a dynamic decrease in two buffer CBPs, CB and PV, following treatment with both compounds in the hippocampus and cerebellum, and also detected a less severe damage by PtAcacDMS compared to CisPt, demonstrating that CBPs can help discriminate between compounds by providing a reliable estimation of neuronal damage [19,39,186,187,188]. Interestingly, contrary to what was observed in hibernating animals, there is no correlation between changes in CBPs and cytoskeletal detection, as CB immunolabelling decreases while NF-H phosphorylation increases following CisPt treatment [18,188], and is likely responsible for the marked morphological signs of degeneration observed in Purkinje cells of the developing rat cerebellum [189].…”
Section: Hibernation and Translational Medicine: The Case Of Neuromentioning
confidence: 99%
“…As mitochondria are important for neuronal Ca 2+ dynamics we suggest that astrocytic mitochondrial transfer is key to normalizing the neuronal mitochondrial network. It remains to be determined whether the normalization of Ca 2+ dynamics results from a direct role of the donated mitochondria in calcium buffering or a secondary effect on other key regulators of calcium homeostatis such as the endoplasmic reticulum (ER), Golgi apparatus, and peroxisomes, or the functioning of ion channels and pumps [55][56][57][58][59]. However, our findings do show that transfer of mitochondria normalizes neuronal Ca 2+ dynamics in neurons damaged by cisplatin.…”
Section: Discussionmentioning
confidence: 64%
“…Additionally, these metallic protrusions can break off during fabrication or use with cell cultures. Although platinum is widely used in biological and medical electrode applications due to its inertness and high electrical conductivity (24), studies have shown that platinum nanoparticles can cause cytotoxic and inflammatory effects in neurons both ex vivo and in vivo (25, 26). Therefore, it is desirable to have uniformly layered platinum deposits without discernible protrusions that could break off.…”
Section: Introductionmentioning
confidence: 99%